5n-3+2n+6=3n+4-7n-9

Simple and best practice solution for 5n-3+2n+6=3n+4-7n-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5n-3+2n+6=3n+4-7n-9 equation:


Simplifying
5n + -3 + 2n + 6 = 3n + 4 + -7n + -9

Reorder the terms:
-3 + 6 + 5n + 2n = 3n + 4 + -7n + -9

Combine like terms: -3 + 6 = 3
3 + 5n + 2n = 3n + 4 + -7n + -9

Combine like terms: 5n + 2n = 7n
3 + 7n = 3n + 4 + -7n + -9

Reorder the terms:
3 + 7n = 4 + -9 + 3n + -7n

Combine like terms: 4 + -9 = -5
3 + 7n = -5 + 3n + -7n

Combine like terms: 3n + -7n = -4n
3 + 7n = -5 + -4n

Solving
3 + 7n = -5 + -4n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '4n' to each side of the equation.
3 + 7n + 4n = -5 + -4n + 4n

Combine like terms: 7n + 4n = 11n
3 + 11n = -5 + -4n + 4n

Combine like terms: -4n + 4n = 0
3 + 11n = -5 + 0
3 + 11n = -5

Add '-3' to each side of the equation.
3 + -3 + 11n = -5 + -3

Combine like terms: 3 + -3 = 0
0 + 11n = -5 + -3
11n = -5 + -3

Combine like terms: -5 + -3 = -8
11n = -8

Divide each side by '11'.
n = -0.7272727273

Simplifying
n = -0.7272727273

See similar equations:

| 3(2x-6)=6(2x+1) | | 4+8=48 | | 6+6*6-6+6= | | f(x)=4x^2-1/9x^2-1 | | 6+6.6-6+6= | | 4=5/ | | x^2-12x+6=-30 | | 5x^2+20x+25=10 | | kx^2-(3k+1)x-15=0 | | kx^2+(3k-1)x-15=0 | | 5x^2-10x-70=5 | | =3-n | | =2n+1 | | 1/x-1/4=2/x | | x^2-2x-8=-7 | | 4x^2-8x-84=8 | | x^2+10x+12=3 | | =5n-20 | | 8m-15=9m+12 | | 1/4m-2m | | 4(x)-3=y | | 5(3-r)+2=3(r+2) | | -4x+21=3x | | -7x+4=2x-5 | | -8x-1=x+26 | | -4x-9=x+1 | | -3w+5=7w-3 | | 12x^4-4x^2-5=0 | | -3x+8=x-4 | | 2a+17=6a+5 | | -3u+10=5u+3 | | 5x+1=12-x |

Equations solver categories